The Knowledge of Families for Dengue Haemorrhagic Fever Prevention at Fatuqueiro Village in Ermera Municipality of Timor Leste - Belo, Ostelino Da Silva; Pinto, Joaquim; Conseição, Jose Ximenes Da; Oqui, Maximiano; Costa, Grados Lino Da (MultiTech Publisher, 2024)
Dengue is a health problem for the population of Timor-Leste and has often occurred and has been destroyed by many people, and dengue in the past is an pandemic of severe dengue disease, but at the moment dengue disease has been a severe disease influenced by environmental factors such as the disposal of waste, poor water sanitation, which has caused a great risk of the occurrence of dengue disease, The Ministry of Health Timor Reported from January to October 2022 with a total of 2.374 cases of dengue with a total of 31 cases fatality rate is 1,3%, the majority of cases detected in Dili Municipality with 1.488 total cases and Ermera municipality is about 90 cases, following by Baucau municipality with 25 cases. Objective of the research is to identify the knowledge of families with dengue prevention at Fatuquero Village. Total 85 families at Fatuquero village in Ermera Municipality, it’s showed only 76,5% of families understand the dengue hemorragic fever (DHF) prevention and the rest of families don’t understand how to prevent dengue hemorragic fever. Also analysis of the Correlation Statistics test showed P-value of 0,000 < 0,5 means that there is a significant relationship knowledge with DHF prevention and r value is 0,946 which is located between 0,0,0-1,00 has showed perfect relationship. The knowledge of families understand how o prevent from DHF is 75,5% and perfect relationship between knowledge of families with DHF prevention by families at Fatuquero village in Ermera Municipality,Timor Leste. The knowledge of families perfect correlation with DHF prevention in Fatuquero village